Existence of Multiple Solutions for a -Kirchhoff Problem with Nonlinear Boundary Conditions - Zonghu Xiu; Caisheng Chen (The Scientific World Journal)
The paper considers the existence of multiple solutions of the singular nonlocal elliptic problem , ,   = , on , where , . By the variational method on the Nehari manifold, we prove that the problem has at least two positive solutions when some conditions are satisfied.